New locality and new habitat data of Philonthus nitidus (Fabr., 1787) (Coleoptera, Staphylinidae) in the Polish Carpathians - Mazur, Andrzej; Yan, Wei; Górz, Andrzej (Zootaxa, 2019)
Philonthus nitidus (Fabr., 1787) inhabits mainly northern and central Europe. In Scandinavia, it reaches far outside the Arctic Circle, in the west it is found in France, in the South in the northern part of the Iberian Peninsula, Italy and Serbia, and in Transylvania; it was also recorded in Siberia, Kazakhstan and Mongolia (Burakowski et al. 1980, Schillhammer 2000, Herman 2001, Löbl & Smetana 2004, Fernández 2010, Viñolas et al. 2014).